2005
DOI: 10.1016/j.jasms.2005.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Direct qualitative analysis of triacylglycerols by electrospray mass spectrometry using a linear ion trap

Abstract: Triacylglycerols (TAGs) isolated from a biological sample provide a challenge for mass spectrometric analysis because of the complexity of naturally occurring TAGs, which may contain different fatty acyl substituents resulting in a large number of molecular species having the identical elemental composition. We have investigated the use of mass spectrometry to obtain unambiguous information as to the individual TAG molecular species present in a complex mixture of triacylglycerols using a linear ion trap mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
151
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(163 citation statements)
references
References 25 publications
11
151
1
Order By: Relevance
“…In spite of this level of both chromatographic and mass spectral separation, each [M+NH 4 ] + was composed of numerous isobaric, yet distinct components. For example, the ion at m/z 876.8, corresponding to TAGs 52:2 (calculated fatty acyl carbon atoms: total number of double bonds), was previously reported to contain over 15 distinct species having unique fatty acyl groups and not counting positional isomers [20]. In part, this can be observed by MS/MS of m/z 876.8 ( Figure 3B…”
Section: Relative Quantitation Of Fatty Acyl Substituents In Dags Andmentioning
confidence: 84%
See 2 more Smart Citations
“…In spite of this level of both chromatographic and mass spectral separation, each [M+NH 4 ] + was composed of numerous isobaric, yet distinct components. For example, the ion at m/z 876.8, corresponding to TAGs 52:2 (calculated fatty acyl carbon atoms: total number of double bonds), was previously reported to contain over 15 distinct species having unique fatty acyl groups and not counting positional isomers [20]. In part, this can be observed by MS/MS of m/z 876.8 ( Figure 3B…”
Section: Relative Quantitation Of Fatty Acyl Substituents In Dags Andmentioning
confidence: 84%
“…For the example, the [M+NH 4 ] + present in this mixture of TAGs observed at m/z 876.8, corresponded to a family of 52:2 TAG species. The MS 2 product ions corresponding to the eight different fatty acyl groups described above were subjected to MS 3 analysis and observed product ions compared to expected product ions for fatty acyl groups 2:0 to 25:2 ( (20). The neutral losses from suspected RC≡O + and/or R′ + 74 ions in the MS 3 mass spectra, the third fatty acyl group was determined (Table 3).…”
Section: Relative Quantitation Of Fatty Acyl Substituents In Dags Andmentioning
confidence: 99%
See 1 more Smart Citation
“…TAGs ammonium adducts were prepared as described by McAnoy et al (2005). Each TAG fraction collected by preparative NARP-HPLC was diluted in 0.5 mL of chloroform/methanol (1:1, v/v) and 25 μL aqueous NH 4 OAc (10 mM) was then added.…”
Section: Esi-ms 3 Analysis Of Triacylglycerolsmentioning
confidence: 99%
“…Although it is widely known that TAGs are hallmarks of RCC, our findings indicated that TAG with different fatty acyl substituents that are not observed in noncancerous tissue could be useful for the application of PESI-MS to cancer diagnosis, as well as to metabolomics underlying the disease [22]. Additionally, sequential and exhaustive ionization of analytes by PESI-MS would guarantee significant potential for the application of mass spectrometry to rapid and real-time clinical diagnosis to guide surgery.…”
Section: Resultsmentioning
confidence: 84%